Existing value addition initiatives enhancing recognition of territorial traits of three Kenyan honey. (8th April 2020) - Warui, Mary W.; Mburu, John; Kironchi, Geoffrey; Gikungu, Mary
Abstract: Recognition of honeys with specific characteristics attributed to their territory (geographical origin) can enhance increased incomes to households in rural areas of Kenya, if protected and sold under Geographical Indications labels. This is mainly because product recognition can result in its demand, reputation, access to market and its protection from imitation and disappearance from the market. Initiatives undertaken by actors in the honey subsector and other sectors to promote recognition of Kenyan honeys and their territorial and local traits have not been documented. This study evaluated the existing value addition initiatives enhancing recognition of territorial or local traits of the three Kenyan honey, that is, honey from Kitui, West Pokot, and Baringo. Data collection methods used included literature review as well as interviews with relevant stakeholders in the honey subsector and other relevant sectors. Results showed that development of honey value chains, product certification, product promotional and marketing activities, and awareness on the link between product quality and geographical origin have greatly contributed to recognition of West Pokot, Baringo, and Kitui honey as well as their territorial traits.